Reimagining sustainable development and economic performance indicators: A human-centric Maslow-Bossel blueprint - Panagiotis Panagiotopoulos; Ioannis Vardopoulos; Marco Maialetti; Clio Ciaschini; Phoebe Koundouri; Luca Salvati (Economies, 2024)
Reflecting the shift from purely quantitative economic growth to broader socio-environmental sustainability, this study proposes a framework for assessing sustainable development (SD) by integrating Maslow's hierarchy of needs with Bossel's classification system. As economic development increasingly emphasizes sustainability, numerous organizations and agencies, including the United Nations, have developed indicators to measure sustainable progress. However, subjective dimensions of SD, grounded in individual values and needs, remain underexplored. This study operationalizes Maslow's 'pyramid of needs' alongside Bossel's system to establish an 'SD pyramid', distinguishing dimensions and indicators that capture social, economic, and environmental complexity. By mapping human needs onto the Sustainable Development Goals (SDGs), this study contributes to delineating (i) the research areas uncovered (or partly covered) with relevant indicators, (ii) a significant lack or partial shortage of pertinent information, and (iii) a combination of a few basic indicators summarizing the necessary information into a unique measure of SD. The outcomes offer a foundation for a quali-quantitative assessment of SD, enhancing the monitoring tools focusing on subjective and contextual needs.
Keywords: 330; sustainable development; performance indicators; sustainability metrics; Maslow's hierarchy; Bossel's classification; economic sustainability; socio-environmental complexity; policy targets; SDGs